Association of Serum Antioxidant Minerals and Type 2 Diabetes Mellitus in Chinese Urban Residents - Jingjing He; Fangyan Chen; Sitong Wan; Yongting Luo; Junjie Luo; Shuli He; Daizhan Zhou; Peng An; Ping Zeng (Antioxidants, 2022)
Antioxidant minerals including zinc, copper and selenium play critical roles in the maintenance of the redox balance in the body. However, their influences on type 2 diabetes mellitus (T2DM) are still inconclusive in Chinese populations. To elucidate the relationship between antioxidant minerals and T2DM, serum zinc, copper and selenium concentrations were measured in 1443 Chinese urban residents using a 1:2 matched case-control study. Conditional logistic regression models (CLR) were used to obtain the odds ratios (ORs) and 95% confidence intervals (CIs), and restricted cubic splines (RCS) were used to examine their dose–response associations. Serum zinc (OR = 0.52 [0.35, 0.77]) and copper concentrations (OR = 0.25 [0.17, 0.37]) were negatively associated with T2DM in a fully adjusted model. An L-shaped zinc-T2DM association (Poverall association = 0.003, and Pnonlinearity = 0.005) and a negative linear copper-T2DM association (Poverall association < 0.0001, and Pnonlinearity = 0.395) were observed. No association was found between serum selenium and T2DM in fully adjusted CLR or RCS models. In addition, joint associations with T2DM were identified between serum zinc and copper and between serum selenium and copper. In conclusion, our study emphasizes the importance of an adequate intake of antioxidant minerals for T2DM prevention in the Chinese population.